A thermodynamic configuration method of combined supercritical CO2 power system for marine engine waste heat recovery based on recuperative effects. (5th January 2022) - Wang, Zhe; Jiang, Yuemao; Han, Fenghui; Yu, Shui; Li, Wenhua; Ji, Yulong; Cai, Wenjian
Graphical abstract: Highlights: A thermodynamic configuration method of supercritical CO2 combined power system is proposed based on recuperative effects. The topping cycle recuperator effectiveness can determine the overall heat distribution and system performance. The recuperator effectiveness is a decision variable of the optimization for the combined system where an optimal solution exists. The proposed method combined with multi-objective optimization can realize an efficient design of relevant systems. Abstract: Supercritical CO2 Brayton cycle (SCBC) is widely used in high-temperature waste heat recovery combined systems with sequential or cascade configurations due to its compact structure and high efficiency. However, since the heat source conditions of these systems are not clearly defined, there is no practicable design approach to comprehensively adapt the waste heat with different temperatures, especially for the ships. This paper aims to propose an effective thermodynamic configuration method to facilitate the design and application of recuperative SCBC combined systems for the high-temperature waste heat recovery of marine engines. To this end, the factors that may affect the system configuration are investigated, and it reveals that the recuperator effectiveness can not only influence its own performance but also determine the heat source conditions, which will finally affect the performance of the entire system. Therefore, a new system configuration method is proposed based on the recuperative effects, and a novel combined system is designed as a case study for further illustration and multi-objective optimization. The results indicate that an optimal value of the recuperator effectiveness exists in the preliminarily determined range, 0.56–0.8. Under the system optimal operating conditions, the total energy output and electricity production cost are 538.97 kW and 5.34 cent/kWh, respectively, and the corresponding thermal and exergy efficiencies research up to 33.17 % and 61.93 %, respectively. It proves that the configuration method proposed in this paper can realize an efficient design of recuperative SCBC combined system, and provide a reference for other relevant systems.